(untitled) (International Journal of Multidisciplinary Research and Creative Innovation Ideas, 2026)
Digital transformation has changed the landscape of the lives of young generations, bringing significant benefits as well as challenges. The intensive use of digital technology can affect their mental health in a complex way. This research aims to understand in depth how young people balance the benefits and challenges of digital transformation with their mental health. This study uses a qualitative method to explore the subjective experiences of the younger generation. Data collection was conducted through in-depth interviews with population sampling techniques involving participants from various social and economic backgrounds, ensuring a broad representation of the experiences of young people, as well as prioritizing a variety of perspectives to gain a rich and comprehensive understanding. The results show that easy access to online information and support provides significant benefits in raising mental health awareness, but exposure to negative content and online social pressures can trigger stress and anxiety. Effective adaptation strategies include screen timing, participation in offline activities, and developing digital literacy skills. In conclusion, digital transformation offers a great opportunity to improve the mental health of the younger generation if managed wisely. The implications of this study emphasize the need for comprehensive digital literacy education programs and strong social support to help the younger generation navigate the digital age healthily. Keywords: Transformation, Digital, Mental Health, Young Generation.